A decrease in functional microbiomes represented as Faecalibacterium affects immune homeostasis in long-term stable liver transplant patients - Soon Kyu Lee; JooYeon Jhun; Seung Yoon Lee; Sukjung Choi; Sun Shim Choi; Myeong Soo Park; Seon-Young Lee; Keun-Hyung Cho; A Ram Lee; Joseph Ahn; Ho Joong Choi; Young Kyoung You; et al. (Gut Microbes)
This study aimed to document the functional microbiome affecting immune homeostasis in long-term post-liver transplantation (LT) patients. We compared the frequency of regulatory T (Treg) and T helper 17 (Th17) cells in the blood and fecal microbiome of 27 LT patients to matched healthy controls (n = 20) using flow cytometry and 16S rRNA sequencing. Among the 27 LT patients, 22 patients ingested immunosuppressants (long-term post-LT group) and five were tolerant patients. The changes in Treg and Th17 cell proportion after treatment with distinct microbiomes in the long-term post-LT group were also examined in vitro . Changes in the identified functional microbiome and Treg cells in tolerant patients were evaluated. The mean time after LT of the included patients was 13.2 y. The gut microbiome of the long-term post-LT group showed lower alpha-diversity (P < .05) with distinct overall microbial composition (P = .001) compared to healthy controls. Among the 11 distinct bacterial genera in abundance, Faecalibacterium was the most decreased in the long-term post-LT group. The long-term post-LT group also demonstrated a decrease in Treg with an increase in Th17 cells, recovered by administration of F. prausnitzii and butyric acid in in vitro analysis. In tolerant patients, Faecalibacterium was marginally increased, coupled with an increase in Treg cells, compared to the long-term post-LT group. In conclusion, the long-term post-LT patients showed a decrease in functional microbiomes represented as Faecalibacterium . These findings provide potential biomarkers for assessing immune status and targets for improving immune homeostasis in LT patients.Abbreviations LT, liver transplantation; HCC, hepatocellular carcinoma; IS, immunosuppressants; DC, dendritic cells; Treg, regulatory T; Th17, T helper 17; AST, aspartate transaminase; ALT, alanine transaminase; OUT, operational taxonomic unit; LEfSe, linear discriminant analysis effect size; LDA, linear discriminant analysis; IL, interleukin; TGF, transforming growth factor; GM-CSF, granulocyte-macrophage colony-stimulating factor; IFN, interferon; TNF-α, tumor necrosis factor-α; MIP-1α, macrophage inflammatory protein-1α; IP-10, interferon γ-induced protein; MCP-1, monocyte chemoattractant protein-1; ACR, acute cellular rejection; NF-κB, nuclear factor κB; PT INR, prothrombin time; QC, quality check; PBMC, peripheral blood mononuclear cells; PBS, phosphate-buffered saline; ELISA, enzyme-linked immunosorbent assay